School Administration: The Key to Success in Modern Educational Management - Meti Fatimah; Mahfud Heru Fatoni; Baron Santoso; Hamid Syarifuddin (Yayasan Adra Karima Hubbi, 2024)
Education management in the modern era is increasingly complex and dynamic, along with technological developments, social change, and the demands of globalization. The purpose of this study is to explore and analyze various approaches to effective school management in modern education management, as well as to recommend models that can be implemented in various types of schools. This study uses a library study method, which is a systematic approach to collecting, analyzing, and analyzing relevant information from various available literature sources. The results of the study concluded that the recommended school management model is a combination of transformational leadership, school-based management, technology utilization, and data-based management. This model allows for flexibility, community participation, and optimal use of resources. In addition, schools must also develop a dynamic and future-oriented curriculum and apply the principle of sustainability in their operations. With this research, it is hoped that it can provide insight for educational leaders, educators, and policy makers in formulating better education management strategies that are relevant to the needs of the times.